Unraveling the association between cotton leafhopper Amrasca (Amrasca) biguttula and leaf morphological traits through stereo microscope and FESEM analysis - MADHU, BANOTH; SIVAKUMAR, SUBBARAYAN; MANICKAM, SADASIVAM; MURUGAN, MARIMUTHU; RAJESWARI, SIVAKAMI; BOOPATHI, NARAYANAN MANIKANDA (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during rainy (kharif) season of 2022 and summer season of 2023 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to identify cotton (Gossypium hirsutum L.) genotypes with enhanced morphological traits to resist leafhopper [Amrasca (Amrasca) biguttula (Shiraki, 1912)] infestations. To achieve this, 5 distinct genotypes were selected as parents, generating 10 F1 hybrids using the half-diallel method. Field and polyhouse experiments were conducted over a 30–120 days-interval. Genotypes, environments, and their interactions (G × E) played a significant role in confirming resistance. Infestation levels varied throughout growth stages, with the highest at 60 DAS (days after sowing). Microscopy analysis revealed glandular trichomes (GTs) and more single-celled non- GTs (NGTs) with complex dendritic branches (2–8) on primary stem leaves. Negative correlations of trichome density, trichome length and gossypol glands with leafhopper populations in both environments suggested a deterrent role. Conversely, leaf thickness positively associated, indicating potential pest preference. Stepwise regression highlighted combination of morphological traits, significantly contributed to greater leafhopper resistance, rather than a single factor. These findings provide valuable insights for selecting and breeding resistant cotton genotypes against leafhoppers.